2005
DOI: 10.1111/j.1471-4159.2005.03387.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular histidine residues identify common structural determinants in the copper/zinc P2X2 receptor modulation

Abstract: To assess the mechanism of P2X 2 receptor modulation by transition metals, the cDNA for the wild-type receptor was injected to Xenopus laevis oocytes and examined 48-72 h later by the two-electrode voltage-clamp technique. Copper was the most potent of the trace metals examined; at 10 lM it evoked a 25-fold potentiation of the 10 lM ATP-gated currents. Zinc, nickel or mercury required 10-fold larger concentrations to cause comparable potentiations, while palladium, cobalt or cadmium averaged only 12-and 3-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…P2X2 receptor. Zinc and copper both exhibit a biphasic effect on rP2X2R function: the ATP-induced responses are significantly potentiated at 10 to 100 M and inhibition at millimolar concentrations (Xiong et al, 1999;Clyne et al, 2002a;He et al, 2003b;Lorca et al, 2005). Zinc also potentiates the ATP responses of native rP2X2Rs and rP2X2/3Rs expressed in neurons from parasympathetic ganglia , as well as in neurons from the rat hypothalamus (Vorobjev et al, 2003) and dorsal motor nucleus (Ueno et al, 2001).…”
Section: A Metals As Allosteric Modulatorsmentioning
confidence: 84%
See 3 more Smart Citations
“…P2X2 receptor. Zinc and copper both exhibit a biphasic effect on rP2X2R function: the ATP-induced responses are significantly potentiated at 10 to 100 M and inhibition at millimolar concentrations (Xiong et al, 1999;Clyne et al, 2002a;He et al, 2003b;Lorca et al, 2005). Zinc also potentiates the ATP responses of native rP2X2Rs and rP2X2/3Rs expressed in neurons from parasympathetic ganglia , as well as in neurons from the rat hypothalamus (Vorobjev et al, 2003) and dorsal motor nucleus (Ueno et al, 2001).…”
Section: A Metals As Allosteric Modulatorsmentioning
confidence: 84%
“…In both cases, the actions of mercury resemble the actions of copper, suggesting that these metals may bind to the same allosteric site. However, this hypothesis was discarded when in was reported that the copper-resistant mutants were still modulated by mercury Lorca et al, 2005). Using chimeric P2X2/X4Rs, we recently found that the primary site of action for mercury is an intracellular cysteine at position 430 (Coddou et al, 2009 P2X7R Virginio et al, 1997).…”
Section: Activation and Regulation Of P2xrsmentioning
confidence: 99%
See 2 more Smart Citations
“…The superimposition of closed and open structures revealed that the RF domain does not undergo conformational changes during the channel gating of P2X receptors ( Figure 2F); however, it does not imply that the RF domain is irrelevant to channel gating. One piece of evidence is that H245, a residue in the RF domain of rP2X2, is involved in zinc/copper potentiation [60] . E249K (rP2X4 numbering) shows sensitivity to PPADS, a chemical that has no effect on the wild-type rP2X4 receptor [61] , indicating that RF may act as an anchor when PPADS binds to the channel.…”
Section: Right Flipper Domainmentioning
confidence: 99%